Mutations in the glutamine synthetase I (GsI) gene produce embryo-lethal female sterility in Drosophila melanogaster. - Caggese, C.; Caizzi, R.; Barsanti, P.; Bozzetti, M.P. (Developmental Genetics, 1992)
A female-sterile mutation (fs(2) PM11-19) was recovered in a screen for P-M hybrid dysgenesis induced mutations uncovered by a deletion of region 21B and was identified as an allele of the gene encoding the Drosophila glutamine synthetase I (GSI) mitochondrial isozyme. Molecular analysis has shown that fs(2)PM11-19 contains a 5 kb insert within 500 bp upstream of the transcriptional start site of the gsI gene. Mutant flies have extremely low levels of gsI transcription and GSI activity. A pre-existing deficiency (Df(2L) netPM1) with a breakpoint near the transcription start site was also found to be a female-sterile allele of gsI. All eggs laid by PM11-19 homozygous females, as well as by females heterozygous for this mutation and a deletion or any of several recessive lethal alleles of the gsI gene, fail to hatch. We conclude that an adequate level of maternally supplied GSI activity is necessary in the early stages of Drosophila embryonic development.